Awareness and Readiness of Librarians towards the Use of Social Media for Information Service Delivery in Higher Institutions of Learning in Bauchi State - Yusuf, Asma’u Muhammad (American International Journal of Social Science Research, 2019)
This paper examines the librarians’ awareness of social media, types of social media used by librarians, perception and readiness of librarians towards the use of social media, the level of use of social media and factors facilitating the use of social media in higher institutions library in Bauchi state. The rationale behind the subject matter (social media) was to expose librarians to the potentials of the use of social media in the library, particularly with regards to effective and efficient information service delivery to meet the ever growing demands and needs of sophisticated users. In doing this, quantitative research methodology using cross-sectional survey design was used which helped the researcher gather large amount of data that can be easily organised and manipulated into reports for analysis. A well developed and structured questionnaire was used to generate data from the respondents.